(untitled) (Journal of Economic Research & Business Administration, 2015)
The article is devoted to the urgent problem of human capital development in the agricultural sector in Kazakhstan. The notion human capital, defined the specifics of its development in agriculture, the dynamics of its development in our country. On the basis of the identified problems conclusions about the future prospects of human capital development as the main driving factor in the innovative economy formation and globalization processes strengthening.